(untitled) (American Journal of Islam and Society, 2008)
The burgeoning cannon of memoirs and fiction written by or about Iranian women has saturated the literary scene of post-9/11America. We have seen literary works translated or mostly written by exiles that entice the curious western reader with Orientalist tales ofMuslim women as veiled, unveiling, powerless victims, or brave escapees of an inherently oppressive patriarchy. The titles and contents of many of these works show that appealing to a specific political climate and power structure is a key factor behind their production, dissemination, and consumption. Therefore, despite this literary boom, it is not certain whether these books add anything to our knowledge of Muslims or if, in fact, they actually obfuscate it. I read several such memoirs while drawing up the required reading lists for the undergraduate courses that I teach at anAmerican liberal arts college. Working under the assumption that exposure to literary self-representation is an effective way of familiarizing students with contemporary Muslim women’s lives, I eventually chose three books written in English by three contemporary Iranian women specifically for western audiences. In its own particular way, each one addresses gender and the experiences of women in Muslim societies: Azar Nafisi’s Reading Lolita in Tehran: A Memoir in Books (Random House: 2003), Fatemeh Keshavarz’s Jasmine and Stars: Reading More Than Lolita in Tehran (University of North Carolina Press: 2007), and Shirin Ebadi’s Iran Awakening: A Woman’s Journey to Reclaim Her Life and Country (Random House: 2007) ...